(untitled) (IUBAT Review, 2024)
The increasing need for tech-savvy professionals is rapidly transforming business education. Many universities are now integrating application software into their courses to better prepare students. This paper explores how incorporating such software can improve students’ skills through hands-on learning experiences. This study uses a qualitative method, gathering primary data through interviews and discussions with participants. It also evaluates students’ strengths and weaknesses in comprehension and analytical skills, using a scenario-based approach for analysis. The results indicate that incorporating application software into business education offers valuable hands-on learning experiences, helping students develop future-ready skills. The study shows that this integration not only enhances students’ skill sets but also boosts digital literacy, critical thinking, and communication skills essential for the modern workplace. In today’s workplace, integrating application software into business education is increasingly important. When combined with experiential learning methods, this software enhances students’ learning and helps them develop essential future skills. This research has limitations, including its focus on qualitative analysis of course-related application software’s impacts. A mixed-methods approach and a cross-university impact assessment could provide more comprehensive and insightful results. IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 125-151